2016
DOI: 10.3389/fphys.2016.00311
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Running Aids to Maintain High Body Temperature in Rats Bred for High Aerobic Capacity

Abstract: The production of heat, i.e., thermogenesis, is a significant component of the metabolic rate, which in turn affects weight gain and health. Thermogenesis is linked to physical activity (PA) level. However, it is not known whether intrinsic exercise capacity, aging, and long-term voluntary running affect core body temperature. Here we use rat models selectively bred to differ in maximal treadmill endurance running capacity (Low capacity runners, LCR and High capacity Runners, HCR), that as adults are divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…The CAE model was established following a previously published protocol ( 14 ). The specific steps were as follows: The treadmill slope was 0°; the training speed was 16 m/min [50–60% maximal oxygen uptake (VO 2 max)]; and the training time was 60 min/day for 5 days/week for a total of 48 weeks ( 15 , 16 ). The IAE model was established following a previously published protocol ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…The CAE model was established following a previously published protocol ( 14 ). The specific steps were as follows: The treadmill slope was 0°; the training speed was 16 m/min [50–60% maximal oxygen uptake (VO 2 max)]; and the training time was 60 min/day for 5 days/week for a total of 48 weeks ( 15 , 16 ). The IAE model was established following a previously published protocol ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Rats were selected for the highest capacity to run (HCR) the longest distances by avoiding mild electric shock during forced, endurance running on a motor-driven treadmill. HCR rats had higher body temperature and a higher metabolic rate, which in turn slowed weight gain and the associated negative health outcomes found in rats born with a low capacity for running, which exhibited higher chronic disease risk (25). HCR rats were more physically active and lost more weight during calorie restriction than the low-capacity runners (26).…”
Section: Discussionmentioning
confidence: 99%
“…After arriving to Finland, rats were tested for maximal running capacity at the age of 9 months with the same speed-ramped running test as described previously [18].…”
Section: Testing Proceduresmentioning
confidence: 99%
“…A recent study in HCRs and LCRs showed that an enhancement of aerobic capacity could mitigate some of the changes in the plasma metabolic profile, which were associated with aging [16]. Concomitantly with higher aerobic capacity, muscle mitochondrial function and oxidative energy metabolism are enhanced in HCRs compared with those in LCRs [17,18]. In addition to skeletal muscle, white adipose tissue (WAT) shares an important role in the regulation of whole body metabolism [19] and WAT-to-muscle communication is critical in overall metabolic health [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation